Citizen perception of gastronomic cultural heritage in tourism management in Jipijapa - Pita Lino, Alexandra Elsy (2023)
This article addresses two sectors whose expansion and growth are marked by their contributions to the socioeconomic and cultural development of the towns: gastronomic cultural heritage and tourism management. The objective is to assess the citizen perception of the gastronomic cultural heritage in the tourist management of the canton of Jipijapa, delving into the economic, social, environmental and cultural analysis. The results showed that the gastronomic cultural heritage in tourism management is remarkable, in the planning, organization, coordination and control of tourism, that tourism management can be improved with the inclusion of the gastronomic cultural heritage, traditions or customs, processes and traditional artisan food preparation techniques and their presence in festive activities as an added value generates new economic income, employment, life change and social well-being, as well as helps to strengthen the gastronomic cultural heritage and tourism management, with the presence of tourist attractions. Keywords: gastronomy, tourism, tourism management, cultural heritage, food, gastronomic heritage.